2009
DOI: 10.1177/0363546509336725
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcome of Open Meniscal Allograft Transplantation

Abstract: Long-term follow-up results show that meniscal allograft transplantation is a beneficial procedure. Good improvements in clinical function and pain relief have been shown at short-term follow-up in this population. Despite the deterioration in function scores over time, there is still improvement in level of function at long-term follow-up but not at a high level. As such, meniscal allograft transplantation is a good salvage option for the treatment of degenerative arthritis of the symptomatic post-meniscectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 29 publications
2
92
0
2
Order By: Relevance
“…14,31,55 Although results are mixed, long-term studies have shown enough benefits to justify the procedure in appropriately indicated patients. 68,69,72,77 To date, 2 survival-analysis investigations of meniscus transplantation have been published. van Arkel and de Boer 68 followed 63 consecutive cryopreserved meniscal transplants 4 to 126 months after surgery.…”
Section: Meniscus Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…14,31,55 Although results are mixed, long-term studies have shown enough benefits to justify the procedure in appropriately indicated patients. 68,69,72,77 To date, 2 survival-analysis investigations of meniscus transplantation have been published. van Arkel and de Boer 68 followed 63 consecutive cryopreserved meniscal transplants 4 to 126 months after surgery.…”
Section: Meniscus Transplantationmentioning
confidence: 99%
“…63,69,73,76,77 The operative techniques and rehabilitation programs remain relatively similar, as do the indications and contraindications. Newer magnetic resonance imaging (MRI) techniques, including use of a 3-T scanner with cartilage-sensitive pulse sequences and T2 mapping, have provid-T T SYNOPSIS: Preservation of meniscal tissue is paramount for long-term joint function, especially in younger patients who are athletically active.…”
mentioning
confidence: 99%
“…Long-term follow-up studies [17][18][19] show a reduction of pain and improved function in the knee after meniscal transplantation.…”
Section: What Are the Results Of Meniscal Tranplantation?mentioning
confidence: 99%
“…Meniscal allograft transplantation (MAT) is performed as a potential biological solution for unicompartmental symptomatic meniscusdeficient patients with early degenerative osteoarthritis [1][2][3]. However, several MAT-related complications reduce the likelihood of successful outcome.…”
Section: Introductionmentioning
confidence: 99%